2023
DOI: 10.1109/tnsre.2023.3254151
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Proprioceptive Reflex Warning Using EMG in Advanced Driving Assistance System

Abstract: A frequent cause of auto accidents is disregarding the proximal traffic of an ego-vehicle during lane changing. Presumably, in a split-second-decision situation we may prevent an accident by predicting the intention of a driver before her action onset using the neural signals data, meanwhile building the perception of surroundings of a vehicle using optical sensors. The prediction of an intended action fused with the perception can generate an instantaneous signal that may replenish the driver's ignorance abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For known environments where the terrain and • Advanced driving assistant system (ADAS) + neuroscience for enhanced vehicle control [59] • Path planning application in unknown and complex environments [2] • Autonomous driving applications [21], [33], [37], [60]- [66] • Intelligent Transportation Systems (ITS) [67] • Gesture recognition for human-vehicle interaction [68] • All-terrain vehicle (ATV) with autonomous navigation and teleoperation [69] • Robust localisation of Autonomous Cars [70] • Socially aware robot navigation [34], [71], [72]…”
Section: W H Eel Ed M Obi L E Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…For known environments where the terrain and • Advanced driving assistant system (ADAS) + neuroscience for enhanced vehicle control [59] • Path planning application in unknown and complex environments [2] • Autonomous driving applications [21], [33], [37], [60]- [66] • Intelligent Transportation Systems (ITS) [67] • Gesture recognition for human-vehicle interaction [68] • All-terrain vehicle (ATV) with autonomous navigation and teleoperation [69] • Robust localisation of Autonomous Cars [70] • Socially aware robot navigation [34], [71], [72]…”
Section: W H Eel Ed M Obi L E Robotmentioning
confidence: 99%
“…They ensure that while a robot remains agile in its movements, it doesn't endanger its integrity or that of its environment. [116], ICP 3 + SVM 4 [132], 2D multi-SLAM [77], GMapping [87], [88], [105], FNN 5 [27], Visual-SLAM + RTAB-Map 6 [126], RTAB-Map [94], Cartographer [65], Monocular SLAM + RL [36], KimeraMulti [133] 2 -Object Detection YOLOv4 7 [62], [103], YOLOv3 [31], [59], [62], YOLOv2 [134], PointNet [135], CNN 8 [21], [23], [136], SVM [137], MobileNet [138], YOLOv2 + JPDA 9 + IMM 10 [139] 3 -Object Tracking…”
Section: Householdmentioning
confidence: 99%
“…Studies such as that by Katsis et al (2008) show that driver distraction is marked by reduced EMG signal amplitude and frequency, making it a useful tool for assessing alertness levels [79]. The work by Hussain et al (2023) expresses the use of EMG for intended action prediction as an addition to the use of cameras and radar-and lidar-based advanced driver assistance systems in AVs [92]. Additionally, the research showcases the effectiveness of the suggested concept through experiments aimed at categorizing online and offline EMG data in real-world environments [92].…”
Section: Electromyography (Emg)mentioning
confidence: 99%
“…The work by Hussain et al (2023) expresses the use of EMG for intended action prediction as an addition to the use of cameras and radar-and lidar-based advanced driver assistance systems in AVs [92]. Additionally, the research showcases the effectiveness of the suggested concept through experiments aimed at categorizing online and offline EMG data in real-world environments [92]. Demonstrating the assessment of a driver's capability to respond to TORs using EMG measurements adequately was exemplified by [93].…”
Section: Electromyography (Emg)mentioning
confidence: 99%